Toxicity Extract and Faction of Surian Toona sinensis Leaf and Bark against Shrimp Larvae Artemia salina L. - Rori Theresia; Syamsul Falah; Mega Safithri; Muhammad Assyar (IPB University, 2016)
Surian (Toona sinensis) is one of the herbs that contain many bioactive compounds. Part of surian plants that can be utilized as therapy is leaf and bark. This study aims to determine the toxicity of leaf and bark extract of Surian through Bhrine Shrimp Lethality Test (BSLT), then compare toxic concentration of water extract, and ethanol 70 %, and n-hexane, diethyl ether and ethyl acetate fractions to shrimp larvae (Artemia salina L). The results showed that water content of leaves simplicia was 8.08 % and bark was 6.26 %. The highest extract rendement value by ethanol solvent was 23 %. The result of BSLT test probit analysis showed that the extract of ethyl acetate bark fraction had the highest toxicity with LC50 value 405.641 ppm, while leaf water extract had the lowest toxicity with LC50 value 707.787 ppm.